The Use of Touch Surgery to Facilitate Knowledge Retention for Dental Students: A Randomized Controlled Trial - Hamza, Tahir. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Periodontology.; Advisor: Irina Dragan.; Committee: Robert Gyurko, Aruna Ramesh, Sarah Pagni, and Michael Newman.; Keywords: Dentistry, and Education.